Influence of prematurity and birth weight on the concentration of ?-tocopherol in colostrum milk - Evellyn Câmara Grilo; Larissa Queiroz de Lira; Roberto Dimenstein; Karla Danielly da S. Ribeiro (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To assess vitamin E levels in the breast milk, analyzing the prematurity and the birth weight influence in α-tocopherol concentration of colostrum milk. METHODS: Cross-sectional study, in which the colostrum was collected from 93 nursing mothers in a public maternity of Natal, Rio Grande do Norte, Northeast Brazil. The newborns were classified based on gestational age and birth weight. The analysis of α-tocopherol in the milk was carried out by high performance liquid chromatography. RESULTS: The α-tocopherol concentration in the colostrum of lactating women whose children were born at term was 1,093.6±532.4µg/dL; for preterm infants, the concentration was 1,321.6±708.5µg/dL (p=0.109). In the preterm group, the α-tocopherol concentration in the colostrum of lactating women whose children were born with low and normal birth weight was 1,316.0±790.7 and 1,327.2±655.0µg/dL, respectively (p=0.971). In the term group, the α-tocopherol levels were higher in mothers of children with birth weight >4000g, being 1,821.0±575.4µg/dL, compared to 869.5±532.1µg/dL and 1,039.6±477.5µg/dL with low and adequate birth weight, respectively (p>0.05). CONCLUSIONS: Prematurity did not influence α-tocopherol levels in the colostrum milk. Mothers who had macrossomic term neonates presented increased α-tocopherol levels. These results indicate that birth weight can influence α-tocopherol leves in the colostrum milk.